The Palmetto State : the making of modern South Carolina - Bass, Jack (University of South Carolina Press, 2012)
As South Carolina enters into the fourth century of its storied existence, the state's captivating, colorful, and controversial history continues to warrant fresh explorations. In this sweeping story of defining episodes in the state's history, accomplished Southern historians Jack Bass and W. Scott Poole trace the key importance of race relations, historical memory, and cultural life in the progress of the Palmetto State from its colonial inception to its present incarnation. The authors bring a strong emphasis on the modern era to their briskly paced narrative, which advances work begun by Bass in his germinal investigation Porgy Comes Home: South Carolina after Three Hundred Years to further our understanding of the state as it now exists. Bass and Poole focus on three central themes-divisions of race and class, adherence to historical memory, and the interconnected strands of economic, social, and political flux-as they illustrate how these threads manifest themselves time and again across the rich tapestry of the South Carolina experience. The authors explore the centrality of race relations, both subtle and direct, in the state's development from the first settlement of Charles Towne to the contemporary political and economic landscape. The tragic histories of slavery and segregation and the struggles to end each in its era have defined much of the state's legacy. The authors argue that conflicts over race continue to influence historical memory in the state, most especially in still-evolving memories-nostalgic for some and ignominious for others-of the Civil War and Reconstruction eras. And they find throughout the state's history a strong role for religion in shaping reaction to changing circumstances. In the discussion of contemporary South Carolina that makes up the majority of this volume, the authors delineate the state's remarkable transformation in the mid-twentieth century, during which a combination of powerful elements blended together through a dynamism fueled by the twin forces of continuity and change. Bass and Poole map the ways through which hard-won economic and civil rights advancements, a succession of progressive state leaders, and federal court mandates operated in tandem to bring a largely peaceful end to the Jim Crow era in South Carolina, in stark contrast to the violence wrought elsewhere in the South. Today there is a growing acceptance of the state's biracial common past and a heartfelt need to understand the significance of this past for the present and future that has come to define the modern Palmetto State. This volume speaks directly to those historical connections and serves as a valuable point of entrance for original inquiries into the state's diverse and complex heritage.